Expression interference of a number of Heterodera avenae conserved genes perturbs nematode parasitic success in Triticum aestivum. (December 2020) - Dutta, Tushar K.; Papolu, Pradeep K.; Singh, Divya; Sreevathsa, Rohini; Rao, Uma
Highlights: in vitro and in vivo reverse-genetics screen was performed to assess RNAi susceptibility of 40 Heterodera avenae target genes. Seven candidate genes were targeted for host-induced gene silencing analysis in Triticum aestivum . transgenic lines were generated that conferred considerable resistance against H. avenae . Abstract: The cereal cyst nematode, Heterodera avenae is distributed worldwide and causes substantial damage in bread wheat, Triticum aestivum . This nematode is extremely difficult to manage because of its prolonged persistence as unhatched eggs encased in cysts. Due to its sustainable and target-specific nature, RNA interference (RNAi)-based strategy has gained unprecedented importance for pest control. To date, RNAi strategy has not been exploited to manage H. avenae in wheat. In the present study, 40 H. avenae target genes with different molecular function were rationally selected for in vitro soaking analysis in order to assess their susceptibility to RNAi. In contrast to target-specific downregulation of 18 genes, 7 genes were upregulated and 15 genes showed unaltered expression (although combinatorial soaking showed some of these genes are RNAi susceptible), suggesting that a few of the target genes were refractory or recalcitrant to RNAi. However, RNAi of 37 of these genes negatively altered nematode behavior in terms of reduced penetration, development and reproduction in wheat. Subsequently, wheat plants were transformed with seven H. avenae target genes (that showed greatest abrogation of nematode parasitic success) for host-induced gene silencing (HIGS) analysis. Transformed plants were molecularly characterized by PCR, RT-qPCR and Southern hybridization. Production of target gene-specific double- and single-stranded RNA (dsRNA/siRNA) was detected in transformed plants. Transgenic expression of galectin, cathepsin L, vap1, serpin, flp12, RanBPM and chitinase genes conferred 33.24–72.4 % reduction in H. avenae multiplication in T1 events with single copy ones exhibiting greatest reduction. A similar degree of resistance observed in T2 plants indicated the consistent HIGS effect in the subsequent generations. Intriguingly, cysts isolated from RNAi plants were of smaller size with translucent cuticle compared to normal size, dark brown control cysts, suggesting H. avenae developmental retardation due to HIGS. Our study reinforces the potential of HIGS to manage nematode problems in crop plant.